Whorkshop penyusunan perangkat pembelajaran berbasis HOTS bagi guru di MA Assawiyah - Fahrurrozi Fahrurrozi; Sri Supiyati; Lalu Muhammad Fauzi; Muhammad Khalqi (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2021)
Since Indonesia participated in the Program for International Students Assessment (PISA) and the Trend in International Mathematics and Science Study (TIMMS) in 2000, the mathematics test results have never been satisfactory. Even until 2018, the results were still unsatisfactory. In other words, the test results are stagnant. To improve the results of these tests, the government has issued a policy of minimum competency assessment (AKM) or known as the Computer-Based National Assessment (ANBK). One of the tests in it is the provision of questions that are included in the Higher Order Thinking Skills (HOTS) category, as are usually given on the PISA and TIMMS tests. Training for teachers in HOTS-integrated learning tools is needed to prepare schools or madrasas to face HOTS-integrated learning. The service partners are all teachers at MA Assawiyah Pringgasela Timur. The community service is on 7-8 August 2021, which 17 teachers attend. The method used is lecture and demonstration. The result of community service activities is that MA Assawiyah teachers gain knowledge about the basic concepts of Higher Order Thinking Skills (HOTS), implementation of HOTS in learning planning, and measuring HOTS in students. This can be seen from the learning tools that have been compiled into the HOTS category.